Revelatory Events : Three Case Studies of the Emergence of New Spiritual Paths - Taves, Ann, 1952- (Book collections on Project MUSE., 2016)
Unseen presences. Apparitions. Hearing voices. Although some people would find such experiences to be distressing and seek clinical help, others perceive them as transformative. Occasionally, these unusual phenomena give rise to new spiritual paths or religious movements. Revelatory Events provides fresh insights into what is perhaps the bedrock of all religious belief--the claim that otherworldly powers are active in human affairs. Ann Taves looks at Mormonism, Alcoholics Anonymous, and A Course in Miracles--three cases in which insiders claimed that a spiritual presence guided the emergence of a new spiritual path. In the 1820s, Joseph Smith, Jr., reportedly translated the Book of Mormon from ancient gold plates unearthed with the help of an angel. Bill Wilson cofounded AA after having an ecstatic experience while hospitalized for alcoholism in 1934. Helen Schucman scribed the words of an inner voice that she attributed to Jesus, which formed the basis of her 1976 best-selling self-study course. In each case, Taves argues, the sense of a guiding presence emerged through a complex, creative interaction between a founding figure with unusual mental abilities and an initial set of collaborators who were drawn into the process by diverse motives of their own. A major work of scholarship, this compelling and accessible book traces the very human processes behind such events.